Draft only: Not for citation. The structure of Russia’s energy sector: Expectations and challenges in Tomsk Oblast - Dusseault, David (Вестник Томского государственного университета. Философия. Социология. Политология)
This paper intends to dig deeper into the Russian energy sector and investigate the relationship between the variable presence of hydrocarbon resources and their influence over policy preferences of regional economic and political elites of Tomsk Oblast in Western Siberia.